1983
DOI: 10.2165/00003088-198308050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methods to Identify Sources of Interindividual Pharmacokinetic Variations

Abstract: The advantages and limitations of the 2 most commonly used methods to investigate interindividual pharmacokinetic variations are reviewed. The first method is based on pharmacokinetic comparisons made after repeated administration of a model drug such as antipyrine, before, during and after imposition of a carefully controlled environmental perturbation. A principal virtue of the test is the use of each subject as a control. Subjects are usually under near basal conditions with respect to factors capable of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 87 publications
1
32
0
Order By: Relevance
“…Confusion occasionally arises between the numerical value of a correlation coefficient and the predictability of that correlation. They are not synonymous: the predictability of one variable based on its correlation to another is not determined by r but by r2 (51), a much lower number than r. The widespread practice of using correlations as proof of a pharmacological relationship, rather than as a clue to design and perform a well-controlled experiment that adequately tests a hypothesis, should be discouraged (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Confusion occasionally arises between the numerical value of a correlation coefficient and the predictability of that correlation. They are not synonymous: the predictability of one variable based on its correlation to another is not determined by r but by r2 (51), a much lower number than r. The widespread practice of using correlations as proof of a pharmacological relationship, rather than as a clue to design and perform a well-controlled experiment that adequately tests a hypothesis, should be discouraged (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of the likelihood surface of the data for uni-or multimodality indicated that the model with the best fit had two modes and raised the possibility that this phenomenon may be under the control of two alleles of major effect at a single autosomal locus, the variation within the modes being due to other genes with comparatively small effects and to other environmental influences (Vesell & Penno, 1983). However, a multimodal distribution only provides very preliminary evidence for a segregating major gene and although the data obtained from the family studies can be interpreted to support the assumption of a genetic mode of inheritance of the impaired sulphoxidation trait, final proof of its existence must await the isolation and characterisation of the specific gene products.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this enzymatic activity is increased in obese individuals, since there is now considerable evidence that subspecies of hepatic cytochrome P-450 may be selectively induced or inhibited with no change in the activity of other subspecies (29). Furthermore, the specific enzyme systems that mediate ibuprpfen biotransformation are not well identified; however, they are resistant to inhibition by cimetidine, which, for all substrates studied to date, has uniformly inhibited cytochrome P-450-mediated drug biotrarisformations in vivo in humans (14).…”
Section: Discussionmentioning
confidence: 99%